2007
DOI: 10.1111/j.1365-2125.2007.02912.x
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine pharmacokinetics in healthy Chinese subjects and effect of the CYP2D6*10 allele

Abstract: What is already known about this subject • Atomoxetine is a cytochrome P450 2D6 (CYP2D6) substrate and its pharmacokinetics has been characterized in a predominantly White population during clinical development. • There are scant East Asian pharmacokinetic data available. • The CYP2D6*10 allele is particularly prevalent in East Asian populations and may contribute to the known ethnic differences in CYP2D6 metabolic capacity. What this study adds • The pharmacokinetics of multiple‐dose 80 mg daily atomoxetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 9 publications
3
45
3
Order By: Relevance
“…Tables 1 and 2 are compilations of single-and multiple-dose pharmacokinetic parameters of atomoxetine in healthy adults displaying different polymorphisms of CYP2D6 and/or CYP2C19 across various races/ethnicities, which were gleaned from the available published literature. As shown in Table 1, the area under the plasma concentration-time curve (AUC) extrapolated to infinity (AUC inf ) and maximum plasma concentration (C max ) generally increased proportionally to dose in both Japanese and United States References: Chalon et al 2003;Cui et al 2007;Matsui et al 2012;Shang et al 2013;and Choi et al 2014. b Data are expressed as mean (% coefficient of variance), unless noted. Belle et al 2002;Sauer et al 2003;Sauer et al 2004;Cui et al 2007;and Matsui et al 2012. b Data are expressed as mean (% coefficient of variance), unless noted.…”
Section: Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tables 1 and 2 are compilations of single-and multiple-dose pharmacokinetic parameters of atomoxetine in healthy adults displaying different polymorphisms of CYP2D6 and/or CYP2C19 across various races/ethnicities, which were gleaned from the available published literature. As shown in Table 1, the area under the plasma concentration-time curve (AUC) extrapolated to infinity (AUC inf ) and maximum plasma concentration (C max ) generally increased proportionally to dose in both Japanese and United States References: Chalon et al 2003;Cui et al 2007;Matsui et al 2012;Shang et al 2013;and Choi et al 2014. b Data are expressed as mean (% coefficient of variance), unless noted. Belle et al 2002;Sauer et al 2003;Sauer et al 2004;Cui et al 2007;and Matsui et al 2012. b Data are expressed as mean (% coefficient of variance), unless noted.…”
Section: Absorptionmentioning
confidence: 99%
“…The oral clearance of the homozygous CYP2D6*10 Japanese subjects were significantly lower than those of the CYP2D6*1/*1, *1/*2, *1/*10 and *2/*10 subjects, and were clearly distinguished from PMs, with the most profound effects noted on clearance in homozygous CYP2D6*10 subjects relative to CYP2D6*1/ *1 and *1/*2 genotypes (Matsui et al 2012). In Chinese subjects, homozygous CYP2D6*10 subjects had, on average, a two-fold higher systemic exposure than the heterozygous CYP2D6*10 and the homozygous CYP2D6*1 subjects (Table 3), as a result of 50% reduction in oral clearance (Cui et al 2007). Likewise, systemic atomoxetine exposure in Korean CYP2D6*10/*10 individuals was approximately threefold greater than that observed in Korean CYP2D6*wt/*wt (*wt = *1 or *2) and *wt/*10 subjects (Byeon et al 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Atomoxetine [7], a highly selective noradrenergic reuptake inhibitor with little affinity for other neurotransmitter systems, is widely used as a drug to treat attention deficit hyperactivity disorder (ADHD) [8] in children, adolescents and adults, which was proved in the United States in 2002. Studies have shown that the prevalence of ADHD was 4.31-5.83% in our country.…”
Section: Introductionmentioning
confidence: 99%
“…Although a predominant role for CYP2D6 in the disposition of ATX has been documented by several studies both in vitro (Ring et al, 2002) and in vivo Cui et al, 2007;Matsui et al, 2012;Brown et al, 2015), other factors also contribute to variability in the dose-exposure relationship, because two-to fivefold variability in apparent oral clearance can be observed within a CYP2D6 genotypepredicted phenotype group in vivo (Matsui et al, 2012;Brown et al, 2015). The objectives of this investigation were threefold: 1) investigate the sources of variability in ATX biotransformation within a CYP2D6 genotype/activity score group; 2) identify other CYP isoforms contributing to ATX biotransformation, particularly in the scenario of lower CYP2D6 activity; and 3) characterize the relative contribution of all pathways of ATX metabolism in a pediatric context, where the influences of CYP genotype, maturation, and development may be evaluated.…”
Section: Discussionmentioning
confidence: 99%